Salicylamide derivative JMX0312 protects immunosuppressed Syrian hamsters against adenovirus lethal challenge - Carretero-Ledesma, Marta; Li, Jun; Martín-Escolano, Javier; Herrera-Espejo, Soraya; Xu, Jimin; Chen, Haiying; Díaz-Navarro, Caridad; Pachón, Jerónimo; Sánchez-Céspedes, Javier; Zhou, Jia; Pachón-Ibáñez, María Eugenia (Antiviral research, 2025)
Despite the fact that human adenovirus (HAdV) causes severe infections in immunosuppressed and immunocompetent individuals, especially in children, there is currently no specific treatment for these infections. Previously we reported a new salicylamide analogue, JMX0312, as a potent inhibitor of HAdV infection with low cytotoxicity in vitro. Here we evaluate the in vivo efficacy and safety of this molecule in the immunosuppressed Syrian hamster model of HAdV infection. JMX0312 administration at a dose of 6.25 mg/kg did not affect the body weight of the animals, and reduced the viral load in liver and blood in a similar way than cidofovir. Also, JMX0312 reduced the mortality of the animals, although in a lesser extent than cidofovir, a drug used to treat these infections that must be subject to rigorous monitoring due to its high toxicity and whose used is not approved in children. Our findings highlight the potential of this new antiviral agent for the treatment of HAdV infections, paving the way for future pre-clinical and clinical trial development towards a safer and more effective treatment against HAdV-associated infections. •HAdV causes life-threatening infections with lack of specific drugs for its treatment.•Cidofovir has limitations such as low bioavailability and nephrotoxicity.•JMX0312 shows potent in vitro anti-HAdV activity with low cytotoxicity.•JMX0312 reduces HAdV viral load in liver and blood without causing significant weight loss.•JMX0312 reduces mortality in the immunosuppressed Syrian hamster model of HAdV.